Systematic Study of Steroid Drugs’ Ability to Cross Biomembranes—The Possible Environmental Impact and Health Risks Associated with Exposure During Pregnancy - Anna W. Sobańska; Aleksandra Orlikowska; Karolina Famulska; Lovro Bošnjak; Domagoj Bosiljevac; Aleksandra Rasztawicka; Andrzej M. Sobański (Membranes, 2024)
Thirty-seven steroid drugs of different types were investigated in silico for their environmental and pharmacokinetic properties (partition between soil and water, bioaccumulation in aquatic organisms, ability to be absorbed from the gastrointestinal tract and to cross biological barriers—skin, blood–brain barrier and placenta) using on-line tools and novel QSAR models. The same drugs were studied by Molecular Docking in the context of their ability to interact with two enzymes—glutathione S-transferase (GST) and human N-acetyltransferase 2 (NAT2), which are involved in the placenta’s protective system against harmful xenobiotics. Steroid drugs are released to the environment from households, hospitals, manufacturing plants and farms (e.g., with natural fertilizers) and they can affect the aquatic life (reproduction and development of aquatic organisms), even at sub-ng/L concentrations. It was established that the majority of studied drugs are mobile in soil, so they may reach surface waters far from point of discharge, e.g., from farming; however, only a few of them are likely to bioaccumulate. All of them can be absorbed orally or through skin, and they are also expected to cross the placenta. Over 30% of studied compounds are likely to pass through the blood–brain barrier (although five compounds in this group are likely P-gp substrates, which may reduce their activity in the central nervous systems); they have also very high affinity for both studied enzymes.